Optimalisasi Rancang Bangun Mesin Mobile Husk Decorticator (Pengupas Tapas Mampu Pindah) untuk Mengolah Tapas Kelapa - Ananto Soebekti, Gamawan; Adi S, Antonius; Budi Setiawan, Albertus; Ramadhany, Reggy (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
A tool called the "Moveable Tapas Peeler" or Mobile Husk Decorticator is used to beat or pound the coconut tapas. This method breaks down the coconut fiber (coconut fiber) and peat (coco peat), which is the fiber created when the coconut tapas is decomposed. Peat is the remaining powder left over from the processed coconut tapas. The purpose of this research is to modify the prototype machine that was previously made because of the unmet production capacity needs and to test the process of modifying the coconut fiber processing by the machine. After the performance of the coconut tapas processing machine has been improved, the machine is expected to be able to achieve production goals, becoming 1) 100 kg / hour; 2) 30 kg / hour of coir fiber production (cocofiber); 3) 70 kg / hour of peat production (cocopeat). The refinement process is based on the Pahl & Beitz design methodology. Working drawings, machine requirements, materials, component standards, and assembly processes determine the machine manufacturing process. The condition of the coconut fiber (dry or soaked) is one of the test factors studied. The crusher speed is 900 rpm and 1260 rpm. This research method is research and development (R & D). The data collection techniques in this study are literature study and observation. The results of the experiment on the coconut processing machine test showed promising performance with the weight of coconut processed reaching 69.67 kg per hour and the coconut fiber produced as much as 169.04 kg per hour. However, the second prototype of this machine still has some shortcomings, especially in terms of coconut fiber decomposition. In this prototype, the coconut fiber has not been completely decomposed during the processing process. As a result, to ensure the quality and uniformity of the final product, an additional filtering machine is needed after the coconut tapas decomposition process. This filtering machine aims to separate coconut fiber that is not properly decomposed so that the final product can meet the quality standards required for sale. The use of this filtering machine is expected to increase the efficiency of the process and the final results of coconut fiber processing, making it more suitable for market needs.